Understanding the role of environmental factors in the development of Systemic Lupus Erythematosus - Parks, Christine G. (Best Pract Res Clin Rheumatol, 2017)
Systemic lupus erythematosus (SLE) is a multisystem disease with a complex etiology. Risk is higher among women, racial and ethnic minorities, and individuals with a family history of SLE or related autoimmune diseases. It is thought that genetic factors interact with environmental exposures throughout the lifespan to influence susceptibility to developing SLE. The strongest epidemiologic evidence exists for increased risk of SLE associated with exposure to crystalline silica, current cigarette smoking, use of oral contraceptives and postmenopausal hormone replacement therapy, while there is an inverse association with alcohol use. Emerging research results suggest possible associations of SLE risk with exposure to solvents, residential and agricultural pesticides, heavy metals, and air pollution. Ultraviolet light, certain infections, and vaccinations have also been hypothesized to be related to SLE risk. Mechanisms linking environmental exposures and SLE include epigenetic modifications resulting from exposures, and increased oxidative stress, systemic inflammation and inflammatory cytokine upregulation, and hormonal effects. Research needs to include new studies of environmental risk factors for SLE generally, with a focus on lifetime exposure assessment, and studies in susceptible subgroups, such as family members or based on genetic risk profiles, or in individuals with evidence of pre-clinical autoimmunity based on detection of specific auto-antibodies. Understanding the role of environmental exposures in the development of SLE may help to identify modifiable risk factors and potential etiologic mechanisms.